ANALYSIS OF THE IMPACT OF PANDAN DURI DAM ON LOWLAND RICE FARMING IN WEST SAKRA SUB DISTRICT EAST LOMBOK REGENCY: ANALISI DAMPAK BENDUNGAN PANDANDURI TERHADAP USAHATANI PADI SAWAH DI KECAMATAN SAKRA BARAT KABUPATEN LOMBOK TIMUR - abdur rahim; Rizal Ahmadi (Fakultas Pertanian, Universitas Gunung Rinjani, 2021)
This study aims to determine the impact of the Pandan Duri dam on changes in the Crop Index (IP) and changes in the productivity level of rice paddy farming in West Sakra District, East Lombok Regency. The method in this research is descriptive, data collection is done by survey technique. Determination of the number of samples as many as 30 people is done by sampling quota and taking farmers in each village is done by proportional random sampling and determining the village as a sample is done by purposive sampling. The results showed that: 1) The total planting index (IP) of lowland rice before the Pandan Duri dam in West Sakra District was 1.39 and after 2.12. This means that the existence of the Pandan Duri dam can have an impact on the difference in the Crop Index (IP) of lowland rice farming in Sakra District and, 2) The average productivity of rice before the Pandan Duri dam in West Sakra District was 49,682 Kw/Ha while after the Pandan Duri dam was 57,267 Kw/Ha and there was a significant difference at the alpha 5% (0,05) level.or in the other word, that the existence of Pandan Duri development has real/significant impact on the productivity of lowland rice farming in West Sakra District, East Lombok Regency